Diagnostics of Progressive Multifocal Leukoencephalopathy in a Patient with Concomitant Lymphoma Infiltration of Central Nervous System During R-CHOP Chemotherapy- A Case Presentation and Review of the Literature. - Kulma-Kreft Monika; Tukaj Cecylia; Rymkiewicz Grzegorz; Śmiałek Urszula; Grabarczyk Piotr; Leśniewski-Kmak Krzysztof; Maciej Zaucha Jan (Journal of Hematology and Oncology Research, 2014)
Progressive multifocal leukoencephalopathy (PML) is a rare complication associated, inter alia, with rituximab-based lymphoma treatment. PML diagnosis is made easier with the criteria recently published by the American Academy of Neurology. Unambiguous diagnosis of PML can be achieved by demonstration of the histopathological triad comprising:(1) demyelination, (2) bizarre astrocytes and (3) enlarged oligodendroglial nuclei together with detection of viral particles by electron microscopy. However, symptoms of PML may be similar to those observed during lymphoma progression into the central nervous system (CNS). Here we report the case of a patient with diffuse large B-cell lymphoma (DLBCL) treated with R-CHOP who developed clinical signs indicating PML. Intravital diagnostic methods failed to yield an unequivocal diagnosis of PML or lymphoma progression in the CNS. However, a post-mortem examination of brain biopsy specimens performed by electron microscopy demonstrated lesions typical for PML and the presence of viral particles. In addition, immunohistochemical assays identified a massive infiltration of lymphoma cells. The case thus suggests either the extremely rare coexistence of two complications: lymphoma CNS infiltration and PML or induction structural CNS lesions by lymphoma infiltration indistinguishable from PML. The presented findings thus highlight the need for a further review of the current diagnostic criteria for PML.
Keywords: central nervous system lymphoma infiltration